Navigating the position of smart bills of lading in international legal framework - Korvenpää, Niina (My University, 2020)
Bills of lading are the most important transport documents in international trade because they serve as documents of title, as an evidence of contract and as a receipt of the traded goods. The document is governed by a number of trade customs and various international conventions. Today, bills of lading still continue to be largely issued and transferred as paper versions which creates costs, delays, and security issues. The largest issues in digitalising bills of lading has had to do with the legal status of the electronic documents as well as the document’s function as a document of title which has been hard to replicate in an electronic setting. However, the distributed ledger technology has been suggested to be the solution to solve the issues that previous platforms have had. The bills of lading issued in the distributed ledger environment are called smart bills of lading. My research question is how the legal status, and especially the validity, of a smart bill of lading will be defined in the framework of the currently available international instruments. The instruments that I will cover are the Hague-Visby Rules, the Rotterdam Rules, and the UNCITRAL Model Law on Electronic Transferable Records. My aim is to clarify the current regulatory situation and to describe the possible future development of the matter on the international level. I will answer to my research question mainly by using the doctrines of sources of international law and interpretation of treaties and use the methods of legal dogmatic and comparative jurisprudence. The effects and legal policies will be analysed as well. In the thesis I will come to the conclusion that the most largely ratified convention, the Hague-Visby Rules is problematic as it has been drafted long before the era of digitalisation, and it has only been used for the paper bills of lading. I think that even through the application of the doctrine of interpretation of treaties and considerations of customary law, the Rules cannot be bent to reliably apply to the world of blockchain. The Rotterdam Rules and the UNCITRAL Model Law on Electronic Transferable Records are both clearly applicable to the smart bills of lading, but their issue is that they have not been largely ratified. International politics affect to the decision of not ratifying the modern rules, and this concerns especially the Rotterdam Rules. The UNCITRAL Model Law is not binding as it is meant to serve as an example for states to use when they modify their national legislation to better fit to electronic commerce. I will come to the conclusion that without any changes to the current rules the status of smart bills of lading as valid documents of title in international trade law is not clear, and the wider incorporation of the Rotterdam Rules and the UNCITRAL Model Law would help to tackle this issue.

Konossementit ovat tärkeimpiä merikuljetusasiakirjoja kansainvälisen kaupan alalla. Ne toimivat sitoumuksina tavaran luovuttamisesta konossementin haltijalle sekä todisteena kuljetusso-pimuksesta ja kuittina sitä koskevasta omaisuudesta. Asiakirjaa sääntelevät monet kauppatavat ja kansainväliset sopimukset. Vielä nykyäänkin konossementit laaditaan usein paperiversioina, mikä aiheuttaa kuluja, viivästyksiä sekä väärinkäytön uhkia. Suurimmat ongelmat konossementin digitalisoinnissa liittyvät elektronisten konossementtien epäselvään oikeudelliseen asemaan sekä siihen, että asiakirja toimii sitoumuksena tavaran luovuttamisesta asiakirjan haltijalle. Kyseistä sitoumusta on ollut haastavaa toteuttaa digitaalisessa ympäristössä riittävällä tavalla. Lohkoketjuteknologiaa on kuitenkin ehdotettu ratkaisuksi tähän ongelmaan. Lohkoketjuympäristössä laadittuja konossementteja kutsutaan älykonossementeiksi. Tutkimuskysymyksenäni on miten älykonossementtien oikeudellinen asema ja erityisesti niiden oikeudellinen pätevyys määritellään tällä hetkellä käytettävissä olevien kansainvälisten instrumenttien perusteella. Työssäni tutkitut instrumentit ovat Haag-Visbyn säännöt, Rotterdamin säännöt ja UNCITRAL:n mallilaki sähköisesti siirrettävistä asiakirjoista (Model Law on Electronic Transferable Records). Tavoitteenani on selventää tämänhetkisen sääntelyn tilannetta sekä kuvailla aiheen mahdollista tulevaisuuden kehitystä. Hyödynnän tutkimuksessa pääasiassa kansainvälisen oikeuden lähteiden sekä kansainvälisten sopimusten tulkinnan doktriineja, ja lisäksi käytän lainopillista metodia sekä teen oikeusvertailua. Analysoin myös aiheeni vaikutuksia ja sääntelytapaa. Tulen työssäni siihen lopputulokseen, että aiheeni kannalta Haag-Visbyn säännöt ovat ongelmallisia niiden laatimisajankohdan takia. Säännöt on laadittu kauan ennen digitalisaation aikakautta, ja niitä on sovellettu ainoastaan paperisiin konossementteihin. Johtopäätökseni on, että kansainvälisten sopimusten tulkinnan doktriinin ja kansainväliseen tapaoikeuteen liittyvien pohdintojen perusteella Haag-Visbyn sääntöjä ei voida kestävällä tavalla soveltaa lohkoketjuteknologian maailmaan konossementtien yhteydessä. Rotterdamin säännöt ja UNCITRAL:n mallilaki taas soveltuvat selvästi myös älykonossementteihin, mutta kumpaakaan instrumenttia ei ole juurikaan ratifioitu. Ratifioimatta jättämiseen vaikuttavat myös politiikan painotukset, erityisesti Rotterdamin sääntöjen kohdalla. UNCITRAL:n mallilaki ei ole luonteelta valtioita sitova, vaan sen tarkoitus on ainoastaan toimia esimerkkinä maiden sääntelyn uudistamiselle. Ilman nykyisten sääntöjen uudistuksia älykonossementtien asema pätevinä asiakirjoina kansainvälisessä kauppaoikeudessa ei ole selvä, mutta Rotterdamin sääntöjen ja UNCITRAL:n mallilain laajempi sisällyttäminen eri maiden oikeussääntöihin muuttaisi tilannetta huomattavasti.
Keywords: international trade law, international law, bill of lading, blockchain, distributed ledger technology kansainvälinen kauppaoikeus, kansainvälinen oikeus, konossementti, merikuljetus-asiakirja, blockchain, lohkoketjuteknologia